Teaching Arabic Body-Part Vocabulary through Meaning Concretization in Islamic Primary Education - Juharoh Juharoh (BASICA, 2025)
This study explores the effectiveness of meaning concretization in teaching Arabic body-part vocabulary in Islamic primary education. Grounded in theories of embodied cognition and meaning-based language learning, the study employs a qualitative classroom-based research design conducted at an Islamic primary school in Indonesia. Data were collected through classroom observations, instructional documents, and teacher reflections to examine how physical demonstration, visual support, and contextual usage influence students’ vocabulary comprehension and engagement. The findings indicate that meaning concretization facilitates deeper semantic understanding by enabling learners to associate Arabic lexical items directly with bodily experience rather than relying on memorization or translation. Students demonstrated improved responsiveness, reduced hesitation, and greater confidence during vocabulary learning activities. In addition to cognitive benefits, concretized instruction fostered positive affective responses, including increased engagement and lower levels of anxiety. These findings suggest that meaning concretization aligns closely with the developmental characteristics of young learners, whose learning processes are strongly grounded in sensory and experiential interaction. The study contributes to Arabic language pedagogy by extending embodied learning perspectives into early vocabulary instruction within Islamic educational contexts. Practically, it offers Arabic teachers a developmentally appropriate and low-cost instructional strategy to enhance vocabulary learning while supporting a positive classroom atmosphere. The study concludes that meaning concretization represents a viable and effective approach for early Arabic vocabulary instruction in Islamic primary education.